PENGARUH FASILITAS PRAKTEK DI SEKOLAH, PERAN DU/DI DAN BURSA KERJA KHUSUS TERHADAP KESIAPAN KERJA SISWA KELAS XII DI SMK NEGERI 2 WONOSOBO KABUPATEN WONOSOBO (JURNAL ILMIAH TUT WURI HANDAYANI, 2016)
The aims of the  research were to determine the influence of practice facilities in schools, the role of DU/DI and special job fair to job readiness of student at Class XII in SMK Negeri 2 Wonosobo of Wonosobo Regency. This research was a quantitative study that explains the phenomenon of research based on the facts that measured quantitative data. Data drawn from the population of all students of class XII SMK Negeri 2 Wonosobo academic year 2014/2015. Total of samples as many as 221 student were taken by proportionale random sampling technique. Instrument of research used questionnaire. Methods of data analysis used of linear regression equation and Partial Correlation. Testing requirements analysis used normality test, linearity, and multicollinearity test with a significance level of 95%.Based on the results, of this study concluded that: (1) There is a significant positive influence on the practice of school facilities, the role of DU / DI and special employment exchange for job readiness of students.. Practice facilities in school, the role of DU/DI and special job fair are the better will improve the job readiness of students. (2) There is a significant positive influence between practice facilities in the school to job readiness of student. Practice in school facilities that will support job readiness students the better. (3) There is a significant positive influence between the role of DU / DI to job readiness of student. The role of DU / DI can better improve the job readiness of students. (4) There is a significant positive influence between the special job fair to the job readiness of student. Special job fair activity that can better improve the job readiness of students. Effective contribution jointly by 55,0%. Individually effective contribution (1) Influence of facility practice in schools on student job readiness for 31,65% , (2) Influence of  role of DU / DI on student work readiness for 28,62 % and (3) Influence of  special job fair to job readiness of students by 39,71% .